2023
DOI: 10.3390/life13040984
|View full text |Cite
|
Sign up to set email alerts
|

Hesperetin and Capecitabine Abate 1,2 Dimethylhydrazine-Induced Colon Carcinogenesis in Wistar Rats via Suppressing Oxidative Stress and Enhancing Antioxidant, Anti-Inflammatory and Apoptotic Actions

Abstract: Colon cancer is a major cause of cancer-related death, with significantly increasing rates of incidence worldwide. The current study was designed to evaluate the anti-carcinogenic effects of hesperetin (HES) alone and in combination with capecitabine (CAP) on 1,2 dimethylhydrazine (DMH)-induced colon carcinogenesis in Wistar rats. The rats were given DMH at 20 mg/kg body weight (b.w.)/week for 12 weeks and were orally treated with HES (25 mg/kg b.w.) and/or CAP (200 mg/kg b.w.) every other day for 8 weeks. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 107 publications
0
1
0
Order By: Relevance
“…Besides, Fisetin induces apoptosis by down-regulating nuclear factor erythroid 2-related factor 2 (Nrf2) in CRC ( Pandey and Trigun, 2023 ). In the same animal model, the study found that Hesperetin reduced the occurrence of CRC induced by 1,2-dimethylhydrazine in Wistar rats by inhibiting oxidative stress, enhancing antioxidant, anti-inflammatory and apoptosis effects ( Hassan et al, 2023 ). Liu F et al reported that the administration of curcumin significantly suppressed the size of xenograft tumors.…”
Section: Application Of Components In Crcmentioning
confidence: 99%
“…Besides, Fisetin induces apoptosis by down-regulating nuclear factor erythroid 2-related factor 2 (Nrf2) in CRC ( Pandey and Trigun, 2023 ). In the same animal model, the study found that Hesperetin reduced the occurrence of CRC induced by 1,2-dimethylhydrazine in Wistar rats by inhibiting oxidative stress, enhancing antioxidant, anti-inflammatory and apoptosis effects ( Hassan et al, 2023 ). Liu F et al reported that the administration of curcumin significantly suppressed the size of xenograft tumors.…”
Section: Application Of Components In Crcmentioning
confidence: 99%